KRISIS KESETARAAN, KEADILAN DAN KRISIS KEMANUSIAAN - Wahab, Gusnarib; Kahar, M. Iksan (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Islam sees gender equality, namely how humans are able to position themselves in their natural roles and functions. Where humans understand the existence of men and women with all their natural essence, not from their weakness but from their strength in carrying out their human vision and mission. Remembering that the essence of justice in gender relations lies in the equality between rights and obligations. Men and women are humans. However, they are different in their natural functions and roles, it would be an injustice if something different were equated in existence. Gender problems are a central issue and theme that is popularly discussed in today's society. Gender definitions can be categorized into three forms; workload, gender roles and gender relations. Etymologically, it means gender. Gender as an analytical tool is commonly used by adherents of the conflict-focused school of social science. Gender is a difference that is not biological and is not God's nature. Biological differences and gender differences are God's nature so they are permanently different. Justice in the Qur'an covers all aspects of human life, both as individuals and as a society. It can be seen that in fact the Qur'an already mentions the existence of justice and equality between men and women in Islam. However, in everyday reality, justice and gender equality as guaranteed in the Al-Qur'an can be said to be still far from expectations, including the implementation that occurs in a world where the majority of citizens are Muslim. Mentioned in Law no. 39 of 1999 concerning Human Rights states that the state recognizes and upholds human rights and basic human freedoms as those which are naturally inherent in and inseparable from the human being, which must be protected, respected and upheld for the sake of increasing human dignity, welfare and intelligence. as well as justice. The purpose of this writing is to find out; Crisis of equality, justice and humanity. The method in this research uses library research or library research. The results show that.